From Program to Product: Turning Your Code into a Saleable Product - Smolina, Rocky (Apress, 2012)
Programming . . . it’s the most fun you can have with your clothes on. At least for a propeller head like myself. And making a pile of dough doing it—well, what could be better? But getting from an idea and bit of code to a polished product ready for market takes more than great enthusiasm and a couple of cases of high-octane cola. Through hard experience, sometimes expensive and often painful, I have learned what one needs to do to turn an idea for a software product into reality. And that is what this book is all about. The book begins with your idea for a great program and ends with you at the starting line, product in hand, ready for that first day of business and that first sale. I’d like to say that this is a top-down cookbook for success—as orderly as a well-written subroutine. But it isn’t. The software game is simply not that neat. So this book is more of a checklist, covering a wide range of topics—from systems analysis, to legal matters, to how to make your program look good to the customer. You’ll read about the economics of software—pricing, license arrangements, and the like. And get advice on what makes an effective manual, how to test your software, and many other topics you might not have thought about.